(Zlo)raba repo poslov in podobni načini prikrojevanja bančnih bilanc - Keršmanc, Ciril (Revija za kriminalistiko in kriminologijo, 2012)
The ongoing financial crisis mixed with the complexity of the modern financial (sub)system often induces one to a simplified criticism of the entire (sub)system. Even though we can agree on a general level that "something is wrong" the debate ends early on and (too) often does not go beyond this point. However, without a clearly identified problem we are doomed to the so called "vicious frustration cycle". Taking this into account, the paper identifies two specific problematic practices linked to repo transactions and Ioan agreements. In a certain context otherwise completely legal forms of repo transactions and loan agreements, become not only problematic, but potentially illegal. The notorious "Repo 105" transaction is used as a reference point for analyzing a similarly problematic practice of temporary loan agreements in the banking sector with the intent to formally avoid forming special reservations. The primary, if not the sole aim, of both contentious practices is a temporary improvement of the financial metrics and balance sheets, the final goal being a greater (undeserved) yield for the management teams in the form of bonuses and capital gains.
Keywords: abuse of legal form; bank; banka; capital gains; creative accounting; creative compliance; deception; deceptive practice; doctored balance sheets; forensic accounting; forenzično računovodstvo; fraud; goljufija; kapitalski dobiček; kreativno računovodstvo; loan agreement; posojilna pogodba; preslepitev; prevara; prirejena bilanca; repo posli; repo transaction; ustvarjalna skladnost; zloraba pravnih institutov